Highly efficient organic-inorganic poly(3,4-ethylenedioxythiophene)-molybdenum trioxide nanocomposite electrodes for electrochemical supercapacitor - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Applied Physics, 2006)
In this paper, we report a highly efficient organic-inorganic nanocomposite electrode with enhanced double layer capacitance, which has been synthesized using 3,4-ethylenedioxythiophene and crystalline molybdenum trioxide (MoO3) in the presence of an external oxidizing agent. The interlayer spacing of MoO3 upon intercalation expands from 6.93 to 13.46 A and is followed by an exfoliation and restacking process. The resulting nanocomposite is characterized by powder x-ray diffraction, scanning electron microscopy, transmission electron microscopy, x-ray photoelectron spectroscopy, and four probe conductivity measurements. The application potential of this nanocomposite as an electrode material for electrochemical supercapacitors has been investigated, highlighting the unusual enhancement of double layer capacitance of poly(3,4-ethylenedioxythiphene) (PEDOT-MoO3) nanocomposites (similar to 300 F g(-1)) compared to that of pristine MoO3 (similar to 40 mF g(-1)). The improved electrochemical performance is attributed to the intercalation of electronically conducting PEDOT between MoO3 layers with enhanced bidimensionality and an increase in the surface area. (c) 2006 American Institute of Physics.